TEXT COMPLEXITY OF SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS: A SYSTEMIC FUNCTIONAL PERSPECTIVE - Putra, Dhani Aldila (2016)
Textbooks have been considered playing a key role in the process of school education by researchers and educators. The importance to explore the language of textbooks has become more and more recognized. However, Nathan et al (2002) claim that though textbooks are the main learning tool, the exploration of textbooks language and composition is rarely to be taken into account for textual studies. The purpose of the present study is to investigate the text complexity progression in the reading texts of English textbooks. The nature and rate of the progression are addressed within the framework of Systemic Functional Linguistics (SFL). Text complexity in this study comprises lexical density, lexical variation, and grammatical intricacy. This study is largely a qualitative design in the form of document analysis. It examines three consecutive grade textbooks issued by the Department of Education and available online for classroom use. Data were collected and sampled from the reading texts found in the textbooks. Data then were analyzed by applying the theories of lexical density, lexical variation and grammatical intricacy in order to find the complexity of the texts. The results of the analyses show that even though the complexity of text within each textbook is found to be inconsistent, it is found that there is a consistent pattern of text complexity progression across grade levels. In other words, the lexical density, lexical variation and grammatical intricacy among the textbooks were found to have consistent progression from one grade level to another of which the directions of the changes are in positive way. It could be concluded that the degree of text complexity of the textbooks becomes higher along with the increase of grade levels to cater for the students' development. --- Buku teks telah dianggap memiliki peranan yang sangat penting dalam proses pendidikan di sekolah oleh para peneliti dan praktisi pendidikan. Keutamaan dalam mengeksplorasi bahasa dari buku teks telah menjadi lebih diperhatikan. Namun, Nathan dkk (2002) menyatakan meskipun buku teks merupakan media pembelajaran utama, penelitian mengenai bahasa dan komposisi bahasa buku teks masih jarang dijadikan sebagai fokus penelitian dalam riset-riset yang berhubungan dengan teks. Tujuan dari studi ini adalah untuk meneliti mengenai perubahan kompleksitas teks dalam teks bacaan yang terdapat di buku teks bahasa Inggris. Hakikat dan tingkatan dari perubahan tersebut ditinjau melalui kerangka Linguistik Sistemik Fungsional (SFL). Dalam studi ini, kompleksitas teks terdiri dari kepadatan leksikal, variasi leksikal, dan kerumitan struktur grammatika. Studi ini secara garis besar merupakan studi kualitatif dalam bentuk analisis dokumen. Tiga buah buku teks yang dikeluarkan oleh Kementrian Pendidikan dijadikan sebagai sumber data dalam studi ini. Data yang diperlukan diambil dari teks bacaan yang ada dalam buku teks tersebut. Data tersebut kemudian dianalisis dengan menerapkan teori-teori mengenai kepadatan leksikal, variasi leksikal, dan kerumitan struktur grammatika untuk menemukan kompleksitas dari teks tersebut. Hasil analisis menunjukkan bahwa meskipun kompleksitas teks dalam masing-masing buku teks ditemukan tidak mengalami peningkatan yang konsisten, kompleksitas teks antara satu buku teks ke buku teks yang lain ditemukan memiliki peningkatan yang konsisten antara satu tingkatan ke tingkatan yang lainnya. Dengan kata lain, kepadatan leksikal, variasi leksikal, dan kerumitan struktur grammatika diantara buku-buku teks tersebut mengalami peningkatan dari satu level ke level yang lainnya. Sehingga dapat disimpulkan kalau tingkatan kompleksitas teks dari buku-buku teks tersebut menjadi lebih tinggi seiring dengan peningkatan level pendidikan untuk menjembatani proses perkembangan siswa.